Exploring Y1 Communications and Services in O-RAN: Background, Privacy, and Security - Sachinkumar B. Mallikarjun; Mohammad Asif Habibi; Mihirraj Dixit; Xavier Costa-Perez; Merouane Debbah; Hans D. Schotten (IEEE Open Journal of the Communications Society)
In the latest open radio access network (O-RAN) architecture, the Y1 interface has been introduced to grant authorized parties, known as Y1 consumers, access to and utilization of Y1 data within the near-real-time RAN intelligent controller (Near-RT RIC). The primary objective of enabling communication between Y1 consumers and the Near-RT RIC is to facilitate the introduction of value-added services to O-RAN. This paper comprehensively explores Y1 communications, services, interface, data, and other essential concepts required to understand the subject matter thoroughly. We examine the security and privacy aspects of Y1 communications to ensure that all authorized parties involved in these interactions are equipped to withstand potential threats and vulnerabilities. More importantly, our research proposes a novel architectural framework for Y1 communications that integrates advanced functionalities and specifies secure communication protocols. This framework addresses the limitations of the state-of-the-art Y1 architecture by enhancing its robustness, adaptability, and efficiency. In addition, we outline the procedural flow for Y1 communications within the proposed framework, detailing the functionalities and processes it introduces. Beyond security and privacy procedures, this paper elaborates on the various phases of Y1 communications. Furthermore, a series of experiments are conducted to evaluate the effectiveness of the proposed Y1 framework. Our assessment focuses on the authentication and authorization schemes, revealing that the mutual transport layer security (mTLS) 1.3-based certificate-bound access token (CBAT) scheme demonstrated superior performance in ensuring secure and efficient communication. Additionally, the robustness of the proposed architecture is validated by evaluating its functionality in both subscription and query scenarios. Moreover, the paper discusses the proposed Y1 framework, primarily focusing on its role and functionality within the Near-RT RIC and its privacy and security considerations. The framework’s performance is thoroughly assessed, particularly the impact of Y1 function placement. Finally, several research challenges are explored, and future directions are identified to provide a roadmap for further advancements and enhancements of the Y1 communications system.